Catalisadores de Co/Al2O3 para reforma a vapor do etanol: estudo do efeito do método de preparação - Garcia, Silmara Rodrigues (2009)
Alumina supported cobalt catalysts were prepared, characterized and applied in ethanol steam reforming for hydrogen production. The support and the supported catalysts were prepared, respectively, by the solvothermal and precipitation, impregnation and deposition-precipitation methods. Contents of 8 and 15% wt of cobalt were used in the preparation of the catalysts. The cobalt was added by impregnation and deposition-precipitation in the Al2O3 supports using a Co(NO3)2.6H2O solution. The solids were characterized by X-Ray Dispersive Spectroscopy (EDX), Temperature-Programmed Reduction with H2 (TPR-H2), X-Ray Diffraction (XRD), BET Nitrogen Adsorption and Temperature Programmed Oxidation (TPO). The results indicated that the preparation method and the treatment conditions of samples were appropriate for obtaining the wanted compounds. Co3O4 phase was verified for all catalysts through analyses of XRD and TPR-H2 results. Catalytic tests were performed by varying the temperature from 450 to 600°C, with water:ethanol molar ratio of 3:1. The ethanol conversion was superior of 99%, with greater hydrogen yield at 600°C. The lower carbon deposition was observed in catalysts prepared with solvothermal/impregnation methods at 450°C.